2006
DOI: 10.1111/j.1365-2958.2006.05475.x
|View full text |Cite
|
Sign up to set email alerts
|

The symbiosis regulator RscS controls the syp gene locus, biofilm formation and symbiotic aggregation by Vibrio fischeri

Abstract: SummarySuccessful colonization of a eukaryotic host by a microbe involves complex microbe-microbe and microbe-host interactions. Previously, we identified in Vibrio fischeri a putative sensor kinase, RscS, required for initiating symbiotic colonization of its squid host Euprymna scolopes. Here, we analysed the role of rscS by isolating an allele, rscS1, with increased activity. Multicopy rscS1 activated transcription of genes within the recently identified symbiosis polysaccharide (syp) cluster. Wild-type cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
258
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(273 citation statements)
references
References 62 publications
9
258
0
Order By: Relevance
“…1). Because this phenotype is similar to the loss of RscS-induced biofilm formation that occurs upon the disruption of structural genes such as sypN, which encodes a putative glycosyltransferase (42,43), we repeated our experiments using an in-frame deletion strain, ⌬sypG. We found that the ⌬sypG mutation also eliminated RscS-mediated attachment (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…1). Because this phenotype is similar to the loss of RscS-induced biofilm formation that occurs upon the disruption of structural genes such as sypN, which encodes a putative glycosyltransferase (42,43), we repeated our experiments using an in-frame deletion strain, ⌬sypG. We found that the ⌬sypG mutation also eliminated RscS-mediated attachment (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Like RscS, multicopy expression of sypG results in enhanced syp transcription and biofilm formation, as measured by glass attachment and pellicle formation (43); however, the pellicles are not as robust as those formed by RscS-overexpressing cells. In addition, the overexpression of SypG does not induce wrinkled-colony formation, another hallmark of RscS overexpression (42). Furthermore, the sypG gene is adjacent to two genes, sypE and sypF, that encode putative SK and RR proteins, respectively; thus, it is not clear whether SypG functions directly downstream of SypF or whether a more complicated regulatory scheme exists.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The islets often encode members of phosphotransferase systems (PTS) and other metabolic genes, suggesting that this strain may encode novel and/or enhanced metabolic capacities that enable the expanded host range relative to MJ11. Absent from SR5 are the ES114-specific biofilm regulator rscS (9,11) and the putative siderophore biosynthesis and receptor genes conserved between MJ11 and ES114 (VF_A0156 to VF_A0165). These observations suggest a number of intriguing issues for future studies as to what biological activities are required for squid colonization and how SR5 is able to efficiently colonize its natural host and the heterologous E. scolopes when MJ11 cannot.…”
mentioning
confidence: 99%